Comparison of DES, AES, IDEA RC4 and Blowfish Aglorithms in Data Encryption and Decryption - Stefanus Eko Prasetyo; Gautama Wijaya; Felix (Politeknik Piksi Ganesha Indonesia, 2025)
The advancement of information technology has had a significant impact, one of which is as a medium for transmitting information from one place to another, making information access easier for many people. However, the ease of access to communication media also poses challenges for information security, as information becomes more vulnerable to being accessed, stolen, or manipulated by irresponsible parties. To protect the confidentiality of information, specific methods are needed, one of which is cryptography. In cryptography, there are various algorithms, including DES, AES, IDEA, Blowfish, Twofish, and RC4. This research aims to compare the performance of several cryptographic algorithms in the data encryption and decryption processes, focusing on processing speed and the size of the encrypted file. The results of the research show differences in processing time and file size of encrypted and decrypted data for each algorithm. Keywords: Aglorithms, Decryption, Encryption.